FACTORS AFFECTING CONSUMERSâ LOCAL FRIED CHICKEN PURCHASE DECISIONS - Emaputra, Andrean; Herliansyah, Muhammad Kusumawan (Jurnal Teknologi Technoscientia, 2017)
There were eight local fried chickens in Special Disrict of Yogyakarta. It makes aquestion about what factors cause successful and unsuccessful local fried chicken. Then,a consumer survey that sought the level of customer satisfaction was done using aquestionnaire. The survey involved 242 respondents that had eaten the local friedchicken. The result shows that the easiness of the outlet to be reached by the consumerand the products price that is competitive are the main factors to lead the local friedchicken to be successful in the market place.